Kreativitas Satlantas Aceh Besar Mengemas Pesan-Pesan Komunikasi Persuasif dalam Mensosialisasikan Ketaatan Berlalu lintas - Yazie Rahmadi JZ; Rahmat Saleh (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRAK Skripsi ini berjudul “Kreativitas Komunikasi persuasif Satlantas Aceh Besar mengemas pesan-pesan Komunikasi Persuasif Satlantas Aceh Besar dalam mensosialisasikan ketaatan lalu lintas”. Rumusan masalah dalam penelitian ini adalah bagaimana langkah-langkah kreatif komunikasi persuasif yang dipakai oleh Satlantas Aceh Besar dalam mengemas pesan-pesan untuk mensosialisasikan ketaatan berlalulintas. Tujuan penelitian ini adalah Untuk mengetahui bagaimana kreativitas komunikasi persuasif satlantas Aceh Besar dalam mensosialisasikan ketaatan berlalulintas. Peneltian ini menggunakan Teori SOR. Tipe penelitian ini menggunakan metode penelitian descriptif kualitatif. Peneliti memperoleh data berdasarkan wawancara, observasi, dengan menggunakan teknik penarikan informan secara purposive. Hasil penelitian menunjukkan bahwa langkah-langkah yang dipakai oleh Satlantas Aceh Besar dalam mengemas pesan-pesan komunikasi persuasif yang disosialisasikan untuk ketaatan berlalu lintas antara lain: menentukan komunikator, mengemas pesan-pesan yang kreatif dengan cara membuat konten-konten menarik, seperti video dan spanduk yang unik menggunakan cara penyampaian yang menyenangkan serta bahasa yang mudah di mengerti, menentukan media yang digunakan yaitu media sosial yang paling banyak digunakan saat ini, Instagram, dan sasaran serta efek yang diharapkan agar masyarakat dapat menerima pesan-pesan yang disosialisasikan oleh satlantas Aceh Besar. Kata Kunci: Satlantas, Kreativitas, Komunikasi Persuasif. Abstract This thesis entitled “the creativity persuasive communication of Traffic Aceh Besar Police in forming the messages of Traffic Aceh Besar Police communicative persuasive in socializing the traffic obedience. The formulation of the problem in this study is to find out how the creative persuasive communication steps are used by Traffic Aceh Besar Police in forming the messages in order to socialize obedience traffic. The goal of this research is to find out how the creativity persuasive communication of Traffic Aceh Besar Police in socializing obedience traffic. In this research the researcher used SOR theory. The methodology wich used in this reserach is descriptive qualitative research. In obtaining the data, the researcher used interview and observation with purposive informan withdrawal technique. The result of this study indicate that the steps which used by Satlantas Aceh Besar in forming persuasive communication which socialize in order to traffic obedience, including: determining the communicator, forming the creative messages by making interesting contents, like the unique videos or banners using the interesting delivery method and through choosing the language which easy to be understood and also determing the widely used social medias today, like Instagram. Moreover, the researcher determine the expected goals and effects so that people can receive the mesages which socialized by Traffic Aceh Besar Police.Keywords: Traffic Police, Creativity, Persuasive Communication ABSTRACT Traffic Police of Aceh Besar has particular responsibility in preventing the high traffic of accident cases which implemented the creativity ways in applying a persuasive way in terms of creating attitudes and behavior of society. This type of research used a descriptive qualitative research method, by presenting data in descriptive form into form of narrative, word, expression, opinion and idea which collected by researcher from various sources. The researcher obtained data based on interview from competent interviewes in order to answer the problem statement through using withdrawal of informants techniques purposively. Then through literature study based on the data received from the initiator of creative ideas by the head of traffic unit of Aceh Besar POLRES and also by several members of Aceh Besar traffic police. The research result indicated that the steps which took by Aceh Besar traffict police in forming messages through a persuasive communication which socialized for compliance the traffic, such as: determining communicator, packaging the creative messages to make the interesting content, like the unique videos and banners, through using interesting ways of message delivery and the language which is easy to be understood, determining the media which mostly used now day in social media, like Instagram, and the goals even the expected effects, so that the society can receive the messages which socialized by Aceh Besar Traffic Police. Keywords: Traffic Unit, Creative, Persuasive Communication